Música experimental na performance do grupo paraibano Jaguaribe Carne - Severo, George Glauber Félix (2013)
With a large musical production that carries out different musical formations, the group JAGUARIBE CARNE has a diversified repertoire whose performances are mainly focused in social matters of the urban life. The songs contemplate different musical esthetic, in which they search to call special attention in order to try a critical musical experience on emergent questions of the society and the cultural politics. In musical terms, the group produces a sonority or noise that searches the different, the unexpected, the provocation, that is, it has to do with a musical style that runs away from the recurrent midiatic standards. This work aims to understand the experimentalism as characteristic of prominence in the musical performance of the group JAGUARIBE CARNE , idealized and founded by the brothers and Musicians Paraibanos, Paulo Ró and Pedro Osmar. They will be detached in this work for being the main integrants of the group since its creation. Thus, as base in the used works (BÉHAGUE,1984; SCHECHNER, 2006; COOK, 2006; MADRID, 2009), I understand as performance any human being activity in which a reflection is done on its means and relationships with the society. From the music point of view , the performance congregates not only the event in itself (hearing and artists), but all the previous technician procedures to the situation of the presentation or writing and the posterior unfolding to this occasion, as critical musical comedies, stories, colloquies, listening, memories, among other aspects. The methodological course developed in this work finds consonance with the particularities of the case study. In this way, as instrument of collection of data had been used, the documentary research, photographs, bibliographical research, discografic-fonograph research, interviews and participant comment. These data, later, had been categorized and analyzed with sights to help the understanding of the studied subject. By ways of analyses, it was possible to verify that in the compositions of the group there is not the concern in contemplating musical formal requirements, whose songs are carried through in accordance with their informal learning‟s by means of debates, listening, readings, performance in social projects, where participants of the Group makes a re-reading of these information in accordance with their spontaneous aims. The experimental character in their songs has also the objective to repudiate the commercial relations of the cultural market and to propose a musical aesthetic that is innovative in terms of musical -sonority and compromised with the social conflicts. Thus, the Group makes use of genres popular and folkloric from various countries and it joins them to a global sonority, with the erudite musical vanguards and to the engaged speech of the songs of national - popular one, generating, a species of sonorous des-construction of these genres.